Analysis of Sources of Distress Among Patients Undergoing Surgery for Colorectal Cancer in Pakistan (Medical Forum Monthly, 2020)
Objective: To find the sources of distress among patients undergoing surgery for colorectal cancer in Pakistan.Study Design: Analytic study.Place and Duration of Study: This study was conducted at the Department of General Surgery, at DHQ Teaching Hospital Gujranwala during March 2019 till November 2019,Materials and Methods: This study was done with the permission of ethical committee of hospital and with the permission of patients. Total 50 patients of colorectal cancer were selected for this study.Results: The consequences of distress screening through the polls are appeared in Table 2. Among the 50 patients, 10 (33.6%) were distinguished as patients with mental distress. Utilizing the MDT, 20 patients detailed sleep deprivation (21.8%), 69 nervousness (30.1%), or 20 discouragement (29.7%). The quantity of patients who scored over the cutoff esteem in HADS-A, HADS-D, and CES-D was 62 (27.1%), 92 (40.2%), and 76 (33.2%), individually.Conclusion: It is concluded that psychological distress is a common factor among cancer patients.